New diagnostic and classification criteria for diabetes mellitus - Paiva, Clara (2000)
In June of 1997, an international expert committee,«Expert Committee on the Diagnosis andClassification of Diabetes Mellitus», under thesponsorship of the «American Diabetes Association»(ADA), published a report with new recommendations for the classification and diagnosis of DiabetesMellitus. The proposed alterations to traditionalpractices, highlight how much has been learned about Diabetes in the last 20 years or so. This subjecthas been studied by the «National Diabetes DataGroup» (NDDG) in 1979, by the «World HealthOrganization» (WHO) in 1980 and therecomendations slightly modified in 1985. The mostsignificant developments in the field have beenregarding the aetiology and pathogenesis of diabetes,as well as a greater knowledge on the predictivevalue of different blood glucose values for the latercomplications of diabetes. New recommendationsinclude the preferred use of the terms « type 1» and«type 2» instead of Insulin Dependent DiabetesMellitus (IDDM) and No – Insulin DependentDiabetes Mellitus (NIDDM) to designate the twomajor types of diabetes, simplification of thediagnostic criteria to two abnormal fasting plasmadeterminations and a lower cut-off for fasting plasmaglucose (126mg/dlor 7 mmol/l) to confirm the diagnosis.